SEVERITY OF JOBLESS GROWTH IN INDIA AND THE RELEVANCE OF SERVICE SECTOR IN EMPLOYMENT GENERATION - Bose, Tithi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This is a phase when the whole world is facing unemployment. But India is troubled by structural unemployment since independence and the severity has intensified after opening up the economy in 1991. All the academics, politicians and policymakers have been anxious to get a cure of this problem. But the problem is multi-dimensional in India and correlated with different factors like education, skills, demographic pattern, gender, public expenditure and the disparity of different sectors. Therefore, it is hard to get a unique solution to this problem. Here the present study has tried to demonstrate the unemployment pattern and the wage share of the different sectors. On the basis of secondary data from different sources, the present study has tried to forecast the unemployment pattern in different states of India. The study has shown how the service sector can boost employment among the uneducated, unskilled population also.